Dirac CP phases in a 3 + 1 neutrino scenario with $$μ -τ $$ μ - τ symmetry - Eduardo Becerra-García (SpringerOpen, 2021)
Abstract A sterile neutrino in the $$3+1$$ 3 + 1 scheme, where the sterile accounts for neutrino anomalies not explained solely by the weak active neutrinos, arises as a natural source for the breaking of the $$μ -τ $$ μ - τ symmetry suggested by oscillation neutrino data. We explore the predictions for the Dirac CP phases in this scenario, with and without sterile neutrino decay, and show that current limits on $$δ _{CP}$$ δ CP suggest a normal hierarchy and a lightest neutrino scale below 0.1 eV as the most plausible explanation for that, when Majorana phases are null. Other Dirac phases turn out to be non zero as well.